Feminine Sexual Subjectivities: Bodies, Agency and Life History - Bryant, Joanne; Schofield, Toni (Sexualities, 2007)
The relationship between discourse, sex and the body has attracted sustained interest from scholars in sociology and cultural studies over the last 20 years. It is only recently, however, that sociological analyses of sexuality have begun to explore the specificity of the body and its relationship to human agency. This work suggests that, far from serving as a passive surface upon which sexual scripts are inscribed, the body in sexual action is itself a dynamic force in generating sexual subjectivities. This is related to the way in which the praxeological aspects of sex are always corporeal and that corporeality is indivisibly related to individual agency. The specific configuration of sexual practices is central to the making of sexual identities. Indeed, it is through such a configuration that the sexual subject is brought into being. Yet human agency is a central feature of the process, rendering it a project that develops over time. Such an idea is particularly relevant to feminists who are concerned with the way that feminine sexual subjectivity can be theorized as active and desiring. This paper explores the way in which the body is implicated in sex practice and the making of active feminine sexual subjectivities. In doing so, it draws on qualitative data collected from life history interviews with 18 women.